Penerapan Multivariate Adaptive Regression Splines pada Laju Produk Domestik Regional Bruto Menurut Lapangan Usaha di Provinsi Sumatera Utara - Gunandri F. Panggabean; Abil Mansyur (Jurnal Sains dan Teknologi, 2023)
North Sumatra's economic growth often experiences fluctuationsthere are changes in external and internal conditions. Studyit aims to find the Multivariate Adaptive Regression Splines model(MARS) on the GRDP growth rate in North Sumatra according to the fieldbest effort using Generalized Cross Validation (GCV) criteria. Methodquantitative research, where the data used is secondary datataken from the Central Bureau of Statistics of North Sumatra, namely Domestic Product data North Sumatra Regional Gross Regional Gross Domestic Product (GRDP) by business sector. Studyin the form of the best MARS model obtained from the piecewise-cubic model andThe level of importance of the predictor variables to the best modelobtained significantly affect the Growth Rate of Domestic ProductsGross Regional by Business Field in North Sumatra.